Application of Foot Massage Therapy to Overcome Ineffective Breathing Patterns in Chronic Kidney Disease (CKD) Patients - Redha Aulia Janah; Ruris Haristiani (International Journal of Biomedical Nursing Review, 2023)
Introduction: One of the clinical manifestations of Chronic Kidney Disease (CKD) is shortness of breath due to interference with the kidneys which results in disruption of the formation of red blood cells. A decrease in the number of red blood cells will interfere with its function to carry oxygen to peripheral tissues so that it can cause shortness of breath. Shortness of breath alone and can cause problems with ineffective breathing patterns. Nursing actions that can be taken in this case include foot massage therapy which aims to reduce shortness of breath. Research objective: to determine the effectiveness of foot massage therapy on ineffective breathing patterns in Chronic Kidney Disease (CKD) patients. Method: This scientific work uses the case report method which describes the case of Mrs. M with the problem of ineffective breathing pattern nursing in the Adenium Room RSD dr. Soebandi Jember. The intervention was foot massage for 30 minutes in 3 days. Discussion: After the foot massage therapy was carried out within 3 days of treatment, it showed a change in respiratory frequency from scale 2 (severely increased) to scale 4 (simply decreased). Non-pharmacological therapy foot massage can help reduce symptoms of shortness of breath because it can increase the hormone endorphins can affect blood vessels so that blood vessels can widen and will improve blood and lymph circulation which can increase oxygen supply and reduce shortness in patients Conclusion: Actions of foot massage therapy can provide a change in the patient's breathing pattern as seen from the previous respiratory rate from 25 x/minute to 20x/minute, dyspnoea has decreased considerably